2019
DOI: 10.3329/fmcj.v13i2.43641
|View full text |Cite
|
Sign up to set email alerts
|

Letrozole or Clomiphene Citrate for Induction of Ovulation in Patients with Polycystic Ovarian Syndrome: A Prospective Randomized Trial

Abstract: Polycystic Ovarian Syndrome (PCOS) is the most common endocrine disorder responsible for subfertility in young women. The aim of the study was to compare the efficacy of Letrozole over Clomiphene citrate (CC) for ovulation induction in patients with PCOS. It was a prospective randomized trial in a private practice setting. The study period was 3 years, which includes 240 sub fertile patients with PCOS. Patients were divided into two groups. Group-A: 120 patients got Letrozole (2.5 mg) tab, 2 tabs once daily fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
(22 reference statements)
3
3
0
Order By: Relevance
“…In this study, women with PCOS had significantly higher BMI than their healthy counterpart (control group). This finding is in harmony with the findings of the studies carried out by Dumesic et al [6], Al-Shattawi et al [15] and Doh et al [16] ,which also reported high BMI among subjects with PCOS. According to Doh et al [16], they hypothesized that PCOS and obesity act synergistically and independently resulting in insulin resistance (IR).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, women with PCOS had significantly higher BMI than their healthy counterpart (control group). This finding is in harmony with the findings of the studies carried out by Dumesic et al [6], Al-Shattawi et al [15] and Doh et al [16] ,which also reported high BMI among subjects with PCOS. According to Doh et al [16], they hypothesized that PCOS and obesity act synergistically and independently resulting in insulin resistance (IR).…”
Section: Resultssupporting
confidence: 90%
“…This finding is in harmony with the findings of the studies carried out by Dumesic et al [6], Al-Shattawi et al [15] and Doh et al [16] ,which also reported high BMI among subjects with PCOS. According to Doh et al [16], they hypothesized that PCOS and obesity act synergistically and independently resulting in insulin resistance (IR). In Dumesic et al [6] study, they noted that dual-energy X-ray absorptiometry have revealed increased accumulation of central fat in women with PCOS.…”
Section: Resultssupporting
confidence: 90%
“…In our study, the ovulation rate was not statistically significantly different between the two study groups (CC 63.6%, Letrozole 68.1%, p= 0.47) which is similar to the studies by Zeba D et al and Liu C et al 14 , 15 While Amer SA et al, Khakwani M et al, Najafi PZ et al and Sakar et al reported significantly better ovulation in letrozole group. 6 , 10 , 16 , 17 One of the issues with ovulation induction drugs is chances of multiple follicular development and hyperstimulation.…”
Section: Discussionsupporting
confidence: 90%
“…Following this, other RCTs were reported supporting letrozole being better in achieving pregnancy and live birth. 5 , 6 , 14 - 16 Liu C et al and Saha J et al recommend no significant difference in ovulation and pregnancy rate in RCT with both drugs and recommend clomiphene citrate as first line drugs 15 , 18 . Wang R et al and Roque M et al in meta-analysis comprising of 1284 and 3962 patients have demonstrated that Letrozole use resulted in significantly better clinical pregnancy and live birth rate compared to clomiphene citrate in women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation